ANALISIS PENCEMARAN UDARA DAN PEMETAAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KOTA SURAKARTA - Sekartaji, Mega Santi, Heru Subaris K, SKM.,M.Kes, Sri Darnoto S.KM M.PH (2016)
ANALYSIS OF AIR POLLUTION AND CARTOGRAPHY USING GEOGRAPHYCAL INFORMATION SYSTEM IN SURAKARTA ABSTRACT Pollution of air is are of influence sphere problem and public health. The kind of this research is descriptive research using geographycal information system approach. It taken from 5 subdistrict in Surakarta. This research uses 3 parameter of measuring such as NO2, O3, SO2 which work with Environmental Agency (BLH) Surakarta. In 2013-2015 the result is not increases and it is not add more Environmental Quality Standards (BML). The tallest measuring on 2014, there are NO2 in Kolonel Sugiono Street as big as 56,90 µg/m3, parameter O3 in Balekambang Park as big as 15,23 µg/m3, meanwhile on parameter SO2 in Nanas Street as big as 65,5 µg/m3. The result of cartography make us easy to see trends of air pollution from years to years. Key word: Analysis Of Air Pollution, Cartography, Geographycal Information System